Hypertension a clinical guide - Ram, C. Venkata S. (CRC Press, Taylor & Francis Group, 2014)
This book explains the fundamental and practical aspects of hypertension - epidemiology, risk, diagnosis, treatment and secondary causes. It will be valuable for physicians, nurses and allied health professionals with an interest in hypertension whether in primary care, in hospitals or in training.